Kinship systems in South and Southeast Asia : a study - Unny, Govindan 1926 (New Delhi : Vikas Pub. House, 1994)
A comparative study of Nairs from Kerala, India, and Minangkabau (Indonesian people) from West Sumatra.
Includes index.
Bibliography: p. 223-227.
Keywords: Kinship -- Indonesia -- Sumatera Barat; Kinship -- India -- Kerala